Prose poetry in theory and practice - Caldwell, Anne; Hardwick, Oz (New York Routledge, Taylor & Francis Group, 2022)
"Prose Poetry in Theory and Practice vigorously engages with the Why? and the How? of prose poetry, a form that is currently enjoying a surge in popularity. With contributions by both practitioners and academics, this volume seeks to explore how its distinctive properties guide both writer and reader, and to address why this form is so well suited to the early 21st century. With discussion of both classic and less well-known writers, the essays both illuminate prose poetry's distinctive features and explore how this 'outsider' form can offer a unique way of viewing and describing the uncertainties and instabilities which shape our identities and our relationships with our surroundings in the early twenty-first century. Combining insights on the theory and practice of prose poetry, Prose Poetry in Theory and Practice offers a timely and valuable contribution to the development of the form, and its appreciation amongst practitioners and scholars alike. Largely approached from a practitioner perspective, this collection provides vivid snapshots of contemporary debates within the prose poetry field, while actively contributing to the poetics and craft of the form"--
Protean manifestations and diverse shapes : defining and understanding strategies of the contemporary prose poem / Cassandra Atherton and Paul Hetherington -- Prose poetry and the resistance to narrative / Oz Hardwick -- "In the eye of the beholder" : prose poetry in dialogue between reader and poet / Hannah Stone -- Nobody's storybook : reading Russell Edson for the wrong reasons / Nicholas Lauridsen -- "Borders on edges, where skin stops, or begins" : the prose poem's relationship with the discourses of fashion and food, with particular reference to Charles Baudelaire, Gertrude Stein, and Harryette Mullen / Susie Campbell -- The contemporary vernacular : exploring intersections of architecture and prose poetry / Anne Caldwell -- "Image machine" : Gaspar Orozco's Book of the peony and the prose poem sequence as perceptual trick / Helen Tookey -- Writing the prose poem : an insider's perspective on an outsider artform / Ian Seed -- "A form of howling. A form of chanting. A form of looking out for each other" : poetics and politics of the contemporary Indian-English prose poem / Divya Nadkarni -- Collaboration, conversation, and adaptation : the prose poetry project and renga attitude / Jen Webb -- Framing catastrophe : the ekphrastic prose poem / Patrick Wright -- "An interlude suspended" : historical biography through the lens of prose poetry / Edwin Stockdale -- Who are the contemporary symbolists? The prose poem and the decorative subjective approach / Ruth Stacey -- One foot; many places : the prose poem's art of standing still while travelling / Jane Monson.
Includes bibliographical references and index.
Keywords: Poetics; Prose poems -- History and criticism